Prevalence Of Goitre In A Non Endemic Area Of Gujarat - Kumar P (Wolters Kluwer Medknow Publications, 1993)
A cross-sectional, prevalence-based study comprising a community (22.486) and school survey (19.589) in rural Mehsana, North Gujarat (population: 20,37,367) revealed the goiter prevalence as 3.5% and 7.3% respectively. Grading of goiter by Stanburyâ€s classification showed 90% -93% of swelling as mid (ob). Application of Stanburyâ€s criteria over the findings of this study proved the area non-endemic. Prevalence was higher in the school than the age at which prevalence increased in the study area, was delayed to 10 years. Similar to endemic areas, prevalence was higher in females than males in all age groups (except pre-school) and the sex difference was most marked in 15-44 years. A marker (ratio of grade I to ob goiter grade) has also been suggested for long term, intervention-oriented monitoring of non- endemic areas.